Political economy of additional development finance - Anthony Clunies-Ross; John Langmore (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
he paper considers the political obstacles and supports for additional development finance and a number of possible devices through which advantage may be taken of the supports and the obstacles circumvented. It emphasizes the need for effective negotiating alliances among developing-country governments that will draw on support from outside their own ranks. It gives particular attention to the 'innovative' methods by which funds might be mobilized by transnational activity for global disposal within a strategy for the progressive reduction of poverty. In order to eliminate one difficulty it outlines a possible arrangement through which funds so raised might be allocated.
Keywords: F41; O16; N25; 330; development finance; aid; Tobin Tax; global governance; Entwicklungsfinanzierung; Tobinsteuer; Global Governance